A Effect of oxidative stress on the reproductive performance of Hair Goat - Dursun, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Small ruminants are the type of animals that make the most of unsuitable land and contribute significantly to the country’s economy. In order to achieve maximum yield from these animals, it is necessary to optimize nutrition and minimize stress factors. One of the important consequences of management and nutrition has been demonstrated by scientists to be oxidative stress. Oxidative stress affect the normal functioning of many physiological systems. In this study, oxidative stress index (OSI), total oxidation level (TOS) and total antioxidant (TAS) levels were investigated in 20 male and 100 female hair goats during the breeding season (October) and out-of-season (May). Females between the ages of 2-6 years and male hair goats aged 2-4 years were used in the study. The correlation between TAS, TOS, and OSI and fertility was evaluated according to sex and season. TAS, TOS and OSI values in female hair goats in October and May were, respectively; 1.28, 1.34; 11.02, 7.13; 0.87, 0.53; in males 1.32, 1.44; 4.24, 8.84; 0.32, 0.63 μmol/L. As a result, it was concluded that as the TOS level increased, the yield of the offspring decreased, and the increase in the TAS level positively affected the yield of the offspring.